Analyzing Volunteer Motivation In Non-Profit Organization (Case Study: Komunitas tanpa Batas) (Journal of Business and Management, 2021)
Komunitas Tanpa Batas is a non-profit organization that engaged in educating street and marginalized children in Bandung. The problem that experienced by organization is that they do not have good volunteer engagement in retaining volunteers in organization. This problem has resulted in a lack of volunteers who are willing to last until the end of the working period and cause this organization to lack volunteers to provide services. Based on these problems, this study aims to determine the reasons underlying volunteers to join and stay in non-profit organizations; also provide recommendation to management on how they can improve strategies to increase volunteer motivation. This research was conducted quantitatively. The method used in this research are pattern matching and making explanation. The result of this study indicate that volunteers survive due to intrinsic and extrinsic motivation. Then suggestion for management to make volunteers remain in organizations are, (1) make improvements in the recruitment system, (2) making planning and decision related to motivational actions, (3) showing more appreciation to volunteers.Keywords: Non-profit organization, Volunteer, Motivation, Engagement, Intention to stay